Severe acute generalized exanthematous pustulosis with blistering mimicking toxic epidermal necrolysis, associated with a primary mumps infection. (1st August 2014) - Azib, S.; Florin, V.; Fourrier, F.; Delaporte, E.; Staumont‐Sallé, D.
Summary: Acute generalized exanthematous pustulosis (AGEP) is a severe adverse cutaneous reaction, which is mostly due to drugs, but which has also been described as occurring after infections. We report a case of severe AGEP with extensive blistering mimicking toxic epidermal necrolysis (TEN) in a 47‐year‐old woman. This was associated with a life‐threatening primary mumps infection, complicated by perimyocarditis and encephalitis. The recent increase in the incidence of mumps should lead physicians to be aware of the uncommon clinical features and complications of this disease.